2016
DOI: 10.1136/bmj.i5065
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis after surgical replacement with a bioprosthetic aortic valve in patients with severe symptomatic aortic stenosis: systematic review of observational studies

Abstract: Objective To determine the frequency of survival, stroke, atrial fibrillation, structural valve deterioration, and length of hospital stay after surgical replacement of an aortic valve (SAVR) with a bioprosthetic valve in patients with severe symptomatic aortic stenosis.Design Systematic review and meta-analysis of observational studies.Data sources Medline, Embase, PubMed (non-Medline records only), Cochrane Database of Systematic Reviews, and Cochrane CENTRAL from 2002 to June 2016.Study selection Eligible o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 99 publications
2
72
1
5
Order By: Relevance
“…Of course, disadvantages of TAVI, such as paravalvular regurgitation, might offset any beneficial effect of less PPM on LV mass regression and survival 39. In addition, we have robust data on TAVI durability only out to 5 years,49 so it is premature to advocate the use of TAVI to prevent PPM, particularly in younger patients given the durability of modern surgical bioprosthetic valves,50 and the low surgical mortality and morbidity rates at experienced valve centres.…”
Section: Prevention Of Ppmmentioning
confidence: 96%
“…Of course, disadvantages of TAVI, such as paravalvular regurgitation, might offset any beneficial effect of less PPM on LV mass regression and survival 39. In addition, we have robust data on TAVI durability only out to 5 years,49 so it is premature to advocate the use of TAVI to prevent PPM, particularly in younger patients given the durability of modern surgical bioprosthetic valves,50 and the low surgical mortality and morbidity rates at experienced valve centres.…”
Section: Prevention Of Ppmmentioning
confidence: 96%
“…Two systematic reviews and meta-analyses (one for efficacy9 and one for prognosis10) provided the evidence for a guideline panel to make recommendations for use of transcatheter aortic valve implantation (TAVI) and surgical aortic valve replacement (SAVR) 11. The meta-analysis assessing the efficacy of these two therapies showed that TAVI, originally designed for patients at high risk for SAVR, can be extended to low-surgical to moderate-surgical risk patients 10.…”
Section: Examples Of Recent Meta-analysis Impacting Guideline Recommementioning
confidence: 99%
“…The meta-analysis assessing the efficacy of these two therapies showed that TAVI, originally designed for patients at high risk for SAVR, can be extended to low-surgical to moderate-surgical risk patients 10. The prognostic review showed that SAVR valves are durable up to 10 years postimplantation, whereas durability of TAVI valves is highly uncertain.…”
Section: Examples Of Recent Meta-analysis Impacting Guideline Recommementioning
confidence: 99%
“…SVD due to progressive deterioration of valve leaflet tissue is the most common cause of surgical bioprostheses failure. A recent systematic review1 of 93 studies including 53 884 (age 53–92 years) patients with AS that focused on prognosis after SAVR with bioprosthetic valves showed that the median survival among those aged ≤65, 65–75, 75–85 and ≥85 years was 16, 12, 7 and 6 years, respectively. Importantly, the freedom from reoperation for valve dysfunction at 10, 15 and 20 years was 94%, 81.7% and 52%, respectively 1…”
Section: Savr Structural Valve Deteriorationmentioning
confidence: 99%
“…TAVI provides effective relief of valve obstruction with excellent immediate and short-term outcomes. However, long-term (ie >10 years) durability of TAVI, relative to the known durability of surgical bioprosthetic valves,1 also needs to be considered. Indeed, there is, up to now, very few data addressing durability of TAVI beyond 5 years,2 which is particularly important in younger patients and those with few comorbidities who have many remaining expected years of life.…”
mentioning
confidence: 99%